Holistic Approach of Indian Sign Language Prediction Software with Emotion Detection - Mazumder, Dipankar; Das, Upamita; Roy, Hillal Kumar; Nilava Sarkar; Singh, Abhishek Kumar (International Journal of Computer Sciences and Engineering, 2026)
A real-time AI software solution for a holistic approach to recognizing Indian Sign Language (ISL) where elements of ISL such as hand shape, facial expression, orientation, movement etc. are analyzed, recognized, and converted into written text. Sentences are formed by analyzing each sign one by one and overlapping detections are ignored. It is a software solution that a user can run on their system without installing any dependencies. We also use emotion detection to understand what a person is trying to say as any human being will have emotions while they convey their message. The model is also trained with an ideal state whereif no signs are being shown, that is if there are no hand movements, no sign is predicted